1994
DOI: 10.1002/clc.4960170604
|View full text |Cite
|
Sign up to set email alerts
|

Response to upright exercise after cardiac transplantation

Abstract: There is little information on the hemodynamic response to upright exercise in patients who have undergone cardiac transplantation. We compared the hemodynamic and metabolic response to upright bicycle exercise in 11 patients with heart transplants and 12 controls. Patients performed two tests—a steady‐state test with a right heart catheter and a maximal incremental test. During steady‐state exercise at 20% of their predicted maximum workload, patients with heart transplants had a higher (mean ± SD, p < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
2
8
0
3
Order By: Relevance
“…Similarly to that in healthy controls, values rise during the effort test 21,26 . Pulmonary vascular resistance is significantly elevated in transplanted patients at rest and during exercise and decreases during effort in the same manner as in healthy individuals.…”
Section: Work Ratementioning
confidence: 55%
See 4 more Smart Citations
“…Similarly to that in healthy controls, values rise during the effort test 21,26 . Pulmonary vascular resistance is significantly elevated in transplanted patients at rest and during exercise and decreases during effort in the same manner as in healthy individuals.…”
Section: Work Ratementioning
confidence: 55%
“…They demonstrated that the relationship between pulmonary capillary pressure and the index of final diastolic volume (PCP/IVDf) had higher values in transplanted subjects during rest and during exercise, indicating decreased ventricular complacency 21 . Martin et al 26 found similar results in supine, and orthostatic resting, and at 20% maxímal oxygen consumption in transplanted subjectes. The pathogenesis of diastolic dysfunction has not been clarified.…”
mentioning
confidence: 65%
See 3 more Smart Citations